1979
DOI: 10.1002/pssb.2220920106
|View full text |Cite
|
Sign up to set email alerts
|

Electronic g‐factor in Cd3As2

Abstract: Using the Bodnar model, the effective mass, density of states, and g-factor of Cd,As, are calculated.It is found that the g-factor is considerably more anisotropic than the effective mass, but decreases sharply with energy in all directions.Kous avons calculk, A partir du modde de Bodnar, la masse effective, le densiti? d'6tats e t le facteur g de Cd,As,. Nous trouvons que le facteur g est beaucoup plus anisotrope que la masse effective, e t diminiie rapidement en fonction de l'knergie pour toutes les directio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
22
0

Year Published

1981
1981
2002
2002

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(26 citation statements)
references
References 5 publications
4
22
0
Order By: Relevance
“…This is done in what follows by taking n-Cd3As, as an example which is usually grown as degenerate n-type crystals having non-standard energy bands and which also has been relatively much less investigated for its different physical aspects [6 to 161. Incidentally, i t may be noted that, in spite of the tetragonal crystal structure of Cd,As, and the early observation of the conduction band anisotropy by Rosenman [7] [7,10,13] in Cd,As2 have provided strong evidence for the validity of the Bodnar model according to which the conduction band in tetragonal semiconductors has ellipsoidal shape in k-space with the anisotropy dependent on energy. I n fact, the Bodnar model is based on the 12 -p treatment with the assumption of a n inverted band structure and isotropic spin-orbit splitting.…”
Section: Introductionmentioning
confidence: 93%
“…This is done in what follows by taking n-Cd3As, as an example which is usually grown as degenerate n-type crystals having non-standard energy bands and which also has been relatively much less investigated for its different physical aspects [6 to 161. Incidentally, i t may be noted that, in spite of the tetragonal crystal structure of Cd,As, and the early observation of the conduction band anisotropy by Rosenman [7] [7,10,13] in Cd,As2 have provided strong evidence for the validity of the Bodnar model according to which the conduction band in tetragonal semiconductors has ellipsoidal shape in k-space with the anisotropy dependent on energy. I n fact, the Bodnar model is based on the 12 -p treatment with the assumption of a n inverted band structure and isotropic spin-orbit splitting.…”
Section: Introductionmentioning
confidence: 93%
“…Using this dispersion relation, Wallace [12] has shown that the energies of the quantized levels under magnetic quantization (taking spin into account) are determined from the equation…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…The commutation relations for the wave vector components in the primed coordinate system are given by ½k x ; k 0 y ¼ Ài=l 2 , in which l is the usual cyclotron radius measured in natural units [20]. Taking into account these commutation relations, the 8 Â 8 k Á p matrix Hamiltonian reduces to a 2 Â 2 pseudo-matrix Hamiltonian [21][22][23]:…”
Section: Theoretical Modelmentioning
confidence: 99%